The Effectiveness of Financial Management Strategies in Public Primary Schools in the South Africa - et. al., L S Mandlazi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper reports a sequential mixed methods study on the effectiveness of financial management strategies in achieving organisational success and stability in public primary schools in Dwarsloop Circuit, Mpumalanga Province, South Africa. The study involved six schools and a sample of 78 participants, comprising 72 School Governing Body (SGB) members and six primary school managers. The study shows that the South African Schools Act, 1996 and the Public Finance Management Act, 1999, are key legislation used to govern and administer the finances of public schools in South Africa. It was ascertained that SGB members with a background in teaching, had a better understanding of the South African Schools Act, compared to SGB members who were parents without teaching experience. The research further shows that most schools in the Dwarsloop Circuit do not use strict internal controls nor is there clear and consistent segregation of duties as key aspects of financial management. It is recommended that all SGB members undergo mandatory training required to execute their duties effectively. The Department of Education in conjunction with the relevant agencies, should ensure an annual financial audit is conducted of all schools in the Dwarsloop Circuit of Mpumalanga Province.